Destrezas matemáticas básicas en los infantes de básica elemental - Urdiales Berrones, Sabrina Aracely (2024)
The objective of this investigative work was to determine the basic mathematical skills developed in elementary school children of the “San Felipe Neri” Fiscomisional Educational Unit, period 2023 - 2024; due to the acquisition or development of basic mathematical skills, counting, numbering, and operations implies a child with mathematical skills, and these are fundamental for the intellectual growth of children. The research was based on information from primary sources and on the judgment of the researcher, who applied appropriate criteria according to the real situation. The methodology used corresponds to a quantitative approach with a non-experimental design. The research type as the level or scope is descriptive, as the objective is basic, as the location is a field, as the type of study, is transversal. The sample was non-probabilistic and intentional and consisted of 48 infants corresponding to the 2nd year of elementary school at the “San Felipe Neri” Fiscomisional Educational Unit; students whose parents signed the informed consent were considered. The technique used was psychometric, and its instrument was the Test for the Diagnosis of Basic Competencies in Mathematics (Tedi-Math) and it was applied concerning the first year of Primary Education (1st EP) according to the age of 6 years. For the analysis of the information and the interpretation of the data, it was carried out with the techniques suggested in the approach according to the instrument applied, for the data processing, objectivity was used with the Excel program, complemented with the development of statisticians of graphic representation such as: tables and diagrams, of the analysis of each test reflected in the exam, thus being the results obtained globally according to the participation of the students. It was concluded that the development of counting and numbering skills is more developed and is acceptable according to the age of the children, and the skill of arithmetic operations is not so developed, however, it was evident that they are acquiring it progressively.